Study On The Parametters Effect Of Tool Wear For Different Cutting Tool In Turning Process - Ummi Nazahah, Roslan (UTeM, 2009)
Austenitic stainless steel possesses some properties such as low thermal conductivity and high ductility that make them be classified under materials of poor machinability that exhibit a lot of difficulties during cutting. The performance of carbide tools was studied to investigate the tool life and wear behavior at various machining parameters. Coated carbide (WNMG432ECU) and uncoated carbide (WNMG080408) were used in turning Austenitic stainless steel (AISI 304). Machining tests were performed in dry cutting condition at various cutting speeds, feed rates and depth of cut. Full factorial's design of experiment was employed to accommodate the machining parameters. Results show that the wear progression for both type of carbide tools experienced the three stages of wear rate namely initial, gradual and abrupt stages of wear mechanism. Slow wear rate were observed at the combination of three machining parameters which are low cutting speed, feed rate and depth of cut. Generally, coated tool performed better as compared to uncoated tool. A longer tool life was achieved using coated tool.